Severe Acute Respiratory Syndrome Coronavirus -2 (SARS-CoV-2): A Review on Pathophysiology, Diagnosis, and Investigational Therapeuti - Sharma, Rahul; Khokhar, Dharmendra; Gupta, Bhanushree; Saxena, Purnendu; Ghosh, Kallol K.; Geda, Arvind Kumar; Kuca, Kamil (Current Medicinal Chemistry, 2021)
There is a new public health crisis threatening the world with the emergence and spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The disease was later named novel coronavirus disease or COVID-19. It was then declared a pandemic by the World Health Organization on March 11, 2020. The virus originated in bats and was transmitted to humans through unknown intermediary animals in Wuhan, Hubei province, China, in December 2019. As of February 5, 2021, 103 million laboratory-confirmed cases and nearly 2.3 million deaths were reported globally. The number of death tolls continues to rise, and a large number of countries have been forced to maintain social distance in public place and enforce lockdown. As per literature, coronavirus is transmitted human to human or human to animal via airborne droplets. Coronavirus enters the human cell through the membrane ACE-2 exopeptidase receptor. WHO, ECDC, and ICMR advised avoiding public places and close contact with infected persons and pet animals. To date, there is no evidence of any effective treatment for COVID-19. The main therapies being used to treat the disease are antiviral drugs, chloroquine/hydroxychloroquine, and respiratory therapy. Although several therapies have been proposed, quarantine is the only intervention that appears to be effective in decreasing the contagion rate. We conducted a literature review of publicly available information to summarize knowledge about the pathogen and the current epidemic. In the present literature review, the causative agent of the pandemic, epidemiology, pathogenesis, and diagnostic techniques are discussed. Further, currently used treatment, preventive strategies along with vaccine trials and computational tools are all described in detail.
Keywords: diagnosis